Very Delayed Brain Metastasis from a Clear Cell Renal Cell Carcinoma: Report of Two Cases and a Literature Review - Souza, Lucas Rodrigues de; Mollo, Rodolfo Francisco Cardoso; Reis, Baltazar Leão; Giannetti, Alexandre Varella; Quiuqui, Gabriel Filipe Soares; Farkasvolgyi, Barbara (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Clear cell renal cell carcinoma (ccRCC) is the most prevalent primary kidney cancer. Although its relevant capability to disseminate, long-term brain metastasis is very unusual. The present paper describes two cases of delayed brain metastasis: one occipital that occurred 20 years after a radical nephrectomy, and one thalamic after 11 years. An extensive literature review was also carried out, and only 31 cases of delayed brain metastasis from ccRCC were found. The authors provide an analysis of all 33 cases, focusing on clinical, radiological, and histological features, along with current treatment recommendations.
Keywords: late onset disorders; renal cell carcinoma; case report; brain metastasis